SELF-REFERENCE AND THE LIMITS OF THOUGHT - Lucian Constantin PETRAŞ (Studia Universitatis Babeș-Bolyai. Philosophia)
Self-reference and the Limits of Thought. This paper explores the connection between the natural language and a formal language from a particular point of view: self-referential constructions. Such constructions lead to some kind of limits of thought, either in the form of paradoxical constructions (Liar-type or Grelling-type), or in the form of the so called limitative theorems in mathematical logic (e.g. Gödel’s theorem). By deriving Gödel’s significant results from paradoxical constructions the limitative character of such self-referential constructions is preserved, but they open the ways for a new representation of a great variety of arguments in the field of logic, mathematics and philosophy.